UPLC-Q-Orbitrap-MS2 analysis of Moringa oleifera leaf extract and its antioxidant, antibacterial and anti-inflammatory activities - Yan, Guo; Liping, Sun; Yongliang, Zhuang (Natural product research, 2020)
Moringa oleifera leaf acetone extract (MLE) was prepared. Phytochemicals of MLE and their antioxidant, antibacterial, and anti-inflammatory activities were evaluated. Results showed that MLE contained total phenolic content of 20.16 mg gallic acid equivalents/g dry weight. A total of 39 compounds were identified by mass spectrometry. The contents of acetyl-glucomoringin, caffeoylquinic acid, feruloylquinic acid, and coumarylquinic acid were high. MLE had high DPPH· and ABTS *+ scavenging activities and reducing powder. In addition, MLE could effectively inhibit S. aureus and B. subtilis, but little effect on E. coli was found. The anti-inflammatory effect of MLE was evaluated using a lipopolysaccharide (LPS) -induced RAW 264.7 cell model. MLE significantly inhibited nitric oxide (NO) production and inducible NO synthase (iNOS) mRNA levels in LPS-induced RAW 264.7 cells. The inhibitory activity increased in a dose-dependent manner. The bioactivities of MLE were related to its phenolic content and phenolic profiles.